Delivering healthcare services to children with cerebral palsy and their families: a narrative review. (1st September 2014) - Hayles, Emily; Jones, Anne; Harvey, Desley; Plummer, David; Ruston, Sally
Abstract Children with cerebral palsy have complex healthcare needs and often require complex multidisciplinary care. It is important for clinicians to understand which approaches to healthcare service delivery for this population are supported in the literature and how these should be applied in clinical practice. This narrative review aims to identify and review the evidence for current approaches to healthcare service delivery for children with cerebral palsy. Databases were searched using key terms to identify relevant research articles and grey literature from December 2011 to September 2013. Search results were screened and sorted according to inclusion and exclusion criteria. Thirty‐two documents were included for evaluation and their content was analysed thematically. Three current approaches to healthcare service delivery for children with cerebral palsy identified in this narrative review were family‐centred care, the World Health Organisation's International Classification of Functioning, Disability and Health, and collaborative community‐based primary care. However, healthcare services for children with cerebral palsy and their families are inconsistently delivered according to these approaches and the identified guidelines or standards of care for children with cerebral palsy have limited incorporation of these approaches. Future research is required to investigate how these approaches to healthcare service delivery can be integrated into clinical practices to enable clinicians to improve services for this population.